A capacity coordination strategy for converters integrated with active damping functionality - ZHANG Kejia; DING Long; YANG Hu; YANG Jinming; CHEN Wang (Zhejiang dianli)
The active damping device mitigates resonance among multiple converters by creating a virtual resistance. To address the capacity coordination challenge between conventional grid-connected functionality and active damping functionality， an adaptive control strategy for virtual resistance based on Fourier transform to regulate the capacity using active damping functionality. Given that the total capacity demands of converters exceed their overall capacity limit， a capacity coordination strategy is formulated. This strategy defines an objective function for resonance mitigation and imposes a constraint on rated power， leading to the development of a Lagrangian function that determines the resonance suppression weights， thereby achieving coordinated allocation of converter capacity. Experimental results demonstrate that the proposed strategy effectively distributes capacity between the grid-connected function and the active damping function in line with the operational demands of the converters.